2015
DOI: 10.4103/2249-4863.152261
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of overweight and obesity among urban adolescents in Bihar, India

Abstract: Background:For better perception of adolescent overweight and obesity as a global public health problem, systematic collection of baseline data is urgently needed in India.Objective:A community-based study was undertaken for better perception of the prevalence and correlates of obesity in an adolescent urban community in Katihar, Bihar.Materials and Methods:A cross-sectional study was conducted among urban adolescents in the eastern part of India to find out prevalence of overweight and obesity and sociodemogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Studies have variously used the cut-offs recommended by the International Obesity Task Force (IOTF), CDC and occasionally national standards [39][40][41][42]. In subnational studies in India, the prevalence of overweight/obesity in adolescents was 7.8% in urban Gujarat and 15.6% in Uttarakhand using WHO growth reference [43,44]; 21% in urban Bihar using the CDC cut-offs [45]; 11% in urban Haryana [46] and 7.2% in Telangana using IOTF cut-offs [47].A large multi-centric study in affluent school going children (2-17 years) in India estimated the overall prevalence of overweight/obesity as 18.2% by IOTF classification and 23.9% by the WHO standards [48]. A systematic analysis of 1,769 global studies found the prevalence of overweight in children and adolescents in developing countries to have increased in boys from 8.1% (95%CI: 7.7, 8.6) to 12.9% (95%CI: 12.3, 13.5)in boys and from 8.4% (95%CI: 8.1, 8.8) to 13.4% (95%CI: 13.0, 13.9) in girls over 1980 to 2013 [49].…”
Section: Over-nutrition Using Who 2007 Growth Reference In Adolescentsmentioning
confidence: 99%
“…Studies have variously used the cut-offs recommended by the International Obesity Task Force (IOTF), CDC and occasionally national standards [39][40][41][42]. In subnational studies in India, the prevalence of overweight/obesity in adolescents was 7.8% in urban Gujarat and 15.6% in Uttarakhand using WHO growth reference [43,44]; 21% in urban Bihar using the CDC cut-offs [45]; 11% in urban Haryana [46] and 7.2% in Telangana using IOTF cut-offs [47].A large multi-centric study in affluent school going children (2-17 years) in India estimated the overall prevalence of overweight/obesity as 18.2% by IOTF classification and 23.9% by the WHO standards [48]. A systematic analysis of 1,769 global studies found the prevalence of overweight in children and adolescents in developing countries to have increased in boys from 8.1% (95%CI: 7.7, 8.6) to 12.9% (95%CI: 12.3, 13.5)in boys and from 8.4% (95%CI: 8.1, 8.8) to 13.4% (95%CI: 13.0, 13.9) in girls over 1980 to 2013 [49].…”
Section: Over-nutrition Using Who 2007 Growth Reference In Adolescentsmentioning
confidence: 99%
“…Underweight individuals are more likely to have COPD and asthma. A micro-level study conducted in Bihar found that alcohol consumption leads to weight gain, which is one of the portent risks of chronic diseases [37]. Traversy and Chaput (2015) found in their study that recreational alcohol consumption may lead to weight gain if the physical activity does not compensate it [38].…”
Section: Discussionmentioning
confidence: 99%
“…There may be some other factors too that determine health status. Other studies have revealed that consumption of high-energy foods and participation in little physical activity are results of abdominal obesity [21, 37]. A study by Mishra et al (2009) found that overweight/obesity were significant drivers of increased metabolic syndrome and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Restriction fast food intake Ghosh et al 16 Low consumption of vegetables and fruits; consumption of obesogenic (fast food, cold drinks, ice cream, sweets, ghee, butter, and red meat). High consumption of alcohol.…”
Section: Nawab Et Al 15mentioning
confidence: 99%